2018
DOI: 10.3390/ijms19103265
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Signatures of Host Defense Suppression by Plant-Feeding Mites

Abstract: Tomato plants are attacked by diverse herbivorous arthropods, including by cell-content-feeding mites, such as the extreme generalist Tetranychus urticae and specialists like Tetranychus evansi and Aculops lycopersici. Mite feeding induces plant defense responses that reduce mite performance. However, T. evansi and A. lycopersici suppress plant defenses via poorly understood mechanisms and, consequently, maintain a high performance on tomato. On a shared host, T. urticae can be facilitated by either of the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 146 publications
(268 reference statements)
3
40
1
Order By: Relevance
“…As noted in the introduction, a previous study suggested that T. urticae infestation may reduce flavonoid levels in tomato plants (Schimmel et al, ). Here, we did not find that T. urticae reduced overall flavonoid levels in tomato.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…As noted in the introduction, a previous study suggested that T. urticae infestation may reduce flavonoid levels in tomato plants (Schimmel et al, ). Here, we did not find that T. urticae reduced overall flavonoid levels in tomato.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, JA enhanced flavonoid production probably via MYB transcription factors in which MYC2 was shown to have a positive role (Dombrecht et al, ). However, T. urticae feeding resulted in the upregulation of the multiple MYC repressor JASMONATE ZIM DOMAIN (JAZ)‐encoding genes in tomato (Schimmel et al, ), which suggested repression of the flavonoid biosynthetic pathway by T. urticae . Moreover, recent studies indicated that T. urticae infestation upregulated the expression of genes encoding 4‐coumarate‐CoA ligase (Schimmel et al, ; Zhang, Bouwmeester, & Kappers, ), and this enzyme is involved in the final step of the phenylpropanoid pathway to precede SA biosynthesis (Chen, Zheng, Huang, Lai, & Fan, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T. evansi suppress tomato defense downstream of plant hormone accumulation, such that the plant's expression of defense‐associated genes is downregulated to the benefit of the herbivore (Alba et al, 2015; Ataide et al, 2016; Sarmento, Lemos, Bleeker, et al, 2011). In the course of the infestation, such suppression can temporarily result in expression levels of defense genes at or below the plant's housekeeping levels (Sarmento, Lemos, Bleeker, et al, 2011) but for most of the time in an intermediate level of induction (Alba et al, 2015; Schimmel et al, 2018). This suppression is mediated by secreted salivary effector proteins (Jonckheere et al, 2016; Villarroel et al, 2016) that restrain the defense response to levels of induction low enough for the mite to tolerate (Ataide et al, 2016), independent of herbivore‐associated bacteria (Staudacher et al, 2017).…”
Section: Introductionmentioning
confidence: 99%